PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI KELAS VIII SMPN 1 BATUSANGKAR - Shilvia Novita Sari, Drs. Wisdiarman, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2016)
learning strategies type of index card match differ from the outcomes of students in learning taught through conventional strategies in class VIII SMPN 1 Batusangkar. This research is a quantitative research quasi experiment and the design is pretest postest control group design. The technique of data analysis conducted in statistics on the SPSS 16. The result showed that the learning outcomes of students in learning art taught by active learning strategies type of index card match different with the learning outcomes of students taught by conventional strategies in class VIII SMPN 1 Batusangkar. Based on the hypothesis test conducted that the tvalue = 3,031 and ttable = 1,997. This means tvalue > ttable, then Ho is rejected. It can be concluded that the use of active learning strategies type of index card match positive effect on improving student learningoutcomes in learning art in class VIII SMPN 1 Batusangkar.Kata Kunci: hasil belajar, pembelajaran seni rupa, strategi pembelajaranaktif tipe index card match.